2007
DOI: 10.1093/tropej/fmn071
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and Nutritional Characteristics of Infants on PMTCT Programs

Abstract: SummaryObjectives: To compare feeding and nutritional characteristics of infants born to mothers on the prevention of mother to child transmission (PMTCT) programs with infants not in the program. Design: A hospital-based case-control study was used. Setting: The study was conducted in Nsambya hospital, Kampala, Uganda. Subjects: A total of 176 mother/baby pairs were included in the study with 88 from each group. Infants were aged from 3 to 12 months. Results: The percentage of mothers exclusively breastfeedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
2
6
0
1
Order By: Relevance
“…A study in Kenyan infants found that HEU infants had poor nutritional outcomes, especially very high levels of stunting, by 24 months . The prevalence of stunting in the present study between HEU and HUU infants was similar to that found in a study of Ugandan infants enrolled in the PMTCT programme . Our bivariate analysis of the prevalence of stunting and being underweight between HEU and HUU infants is therefore consistent with the larger body of literature.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A study in Kenyan infants found that HEU infants had poor nutritional outcomes, especially very high levels of stunting, by 24 months . The prevalence of stunting in the present study between HEU and HUU infants was similar to that found in a study of Ugandan infants enrolled in the PMTCT programme . Our bivariate analysis of the prevalence of stunting and being underweight between HEU and HUU infants is therefore consistent with the larger body of literature.…”
Section: Discussionsupporting
confidence: 89%
“…Studies conducted in other African countries comparing the nutritional status of HEU and HUU infants show large variations in the levels of undernutrition . The majority of these studies were conducted before antiretroviral therapy (ART) was widely available to mothers and infants . By contrast, ART is available to approximately 92% of pregnant women in Botswana .…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar to cross-sectional findings of Orne-Gliemann et.al., Zimbabwe [33], and Magezi, Uganda [21], who document earlier commencement of MBF and poorer adherence to feeding recommendations, respectively amongst HIV-negative compared with positive women. Furthermore, we show that in 2001-2003 the EBF prevalence at 12 weeks was low - 7.2% and 2.8% amongst breastfeeding HIV-positive women and negative women respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian ini sejalan dengan hasil penelitian Magezi (2011) insiden berat badan lahir rendah memiliki kemungkinan 8.4% mendapatkan bayi HIV dibandingkan dengan berat bayi lahir normal. Menurut Slyker et al, (2014) Tingkat HIV-1RNA ibu hamil berhubungan dengan peningkatan kejadian BBLR.…”
Section: American College Of Obstetricians and Gynecologists (Acog) Dunclassified